METHODOLOGICAL CONTRIBUTION IN THE FIELD OF MOUNTAIN LEISURE ACTIVITIES PRACTICING CASE STUDY: SCRAMBLING IN HIGH TATRAS - Ioan BÎCA; Raoul ZANCA; Eduard SCHUSTER (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2019)
Mountain leisure activities attract many participants because they are beneficial for health, maintain fitness, induce the feeling of performance and are spectacular. Among these activities, stands scrambling, which is part of the mountaineering and it is practice on the rock exposed surfaces (walls, ridges, chimneys, gully). One of the areas that offer excellent conditions for practicing scrambling is High Tatras (Vysoke Tatry) in Slovakia, where granite and gneiss rocks have created an attractive and favorable microrelief for this activity. This study aims at carrying out experimental methodological researches on the route Velička Dolina-Velicky zlab-Gerlachovský peak- Dolina-batizovsle Žlab-Batizovska Dolina-Batizovske Pleso-Sliezsky Dom regarding scrambling organization activity and mentation of specific climbing techniques in correlation with geologic factors (rocks, landforms). The subjects of this experiment were a group of students from the Faculty of Geography, from Babes-Bolyai University Cluj-Napoca (Romania), Tourism Geography specialization, without previous mountaineering experience on stony ground.